Bioequivalence Study of Tramadol by Intramuscular Administration in Healthy Volunteers - Chao, Chih-Kai; Yu, Li-Li; Su, Li-Li; Liu, Chu-Min; Yang, Tsung-Hsien; Chen, Chi-Ming (Arzneimittelforschung, 2000)
Tramadol hydrochloride (CAS 36282-47-0) is a centrally acting analgesic agent binding to μ opiate receptors. The bioavailability of a new tramadol hydrochloride injection (Limadol®) was compared with a commercially available reference product by intramuscular administration in twelve healthy Chinese male volunteers by a standard two-way cross-over trial. Each volunteer received a single 100 mg injection of tramadol HCl in each phase. The bioavailability was compared using the area under the plasma concentration-time curve from time 0 to 30 h (AUC0-30), the area under the plasma concentration-time curve from time 0 to infinity (AUC0-∞), peak plasma concentration (Cmax), and time to reach peak plasma concentration (Tmax). No statistically significant difference was observed between the Tmax, Cmax, AUC0-30 and AUC0-∞ of the two preparations. It is concluded that test and reference formulations of tramadol hydrochloride are bioequivalent for both the extent and rate of absorption after a single intramuscular injection.
Keywords: Analgesics; CAS 36282-47-0; Limadol®, bioavailability, bioequivalence; Tramadol hydrochloride, intramuscular administration